Risk factors and phenytoin prophylaxis for early post-traumatic seizures among patients with traumatic brain injury - Chan, Kin Hup; Tharakan, John; Pal, Hillol Kanti; Khan, Naeem; Tan, Yew Chin (Universiti Sains Malaysia, 2010)
Background: Post-traumatic seizure is a well-known and serious complication of traumatic brain injury (TBI). The incidence and risk factors vary among study populations. Very little data have been published concerning this in the Malaysian population. The aim of this study was to ascertain the risk factors for the development of early post-traumatic seizures among patients with TBI. Methods: This was a prospective observational study, carried out in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan, under the Department of Neurosciences. A total of 157 patients, from all age groups, who were diagnosed with TBI were enrolled from June 2007 to December 2007. They were followed-up for 12 months until death or their first post-traumatic seizure. Survival analysis with Kaplan–Meier curves and Cox proportional hazards regression was performed. Results: A total of 11 (7.0%) of the patients developed early post-traumatic seizures. The risk factors for early post-traumatic seizures were young age (P = 0.021, 95% CI 0.806 to 0.982) and intubated patients (P = 0.029, 95% CI 1.194 to 25.913). The incidence of early post-traumatic seizures in the local population was 7.0%. Conclusion: The incidence of early post-traumatic seizures in the local population of Kelantan and Terengganu is comparable to the incidences reported elsewhere. Younger as well as intubated patients were at a higher risk of developing this condition. It may be necessary to give antiepileptic prophylaxis because any seizure could adversely affect morbidity and mortality. However, the study showed that antiepileptic drug was not beneficial in preventing late post-traumatic seizures, but may have a role in preventing early seizures.